Character Building : Pentingnya Literasi Digital dan Kesehatan Reproduksi Remaja untuk Membentuk Siswa Kelas XI Hebat - Nugroho Adhi Santoso; Bangkit Indarmawan Nugroho; Sarif Surorejo; Aang Alim Murtopo; Rifki Dwi Kurniawan; Syefudin Syefudin; Zaenul Arif; Bayu Aji Santoso (Universitas Veteran Bangun Nusantara Sukoharjo, 2024)
The abundance of information available in the digital world makes it difficult for students to sort out what is true and relevant. Many teenagers get information about reproductive health from unreliable sources or even myths. The lack of good role models can make teenagers lose their way. Equip students with the skills to evaluate information, think critically, and use technology responsibly. Grade XI students are at a critical stage of development. They are starting to form their identity, make more independent decisions, and prepare themselves for the future. Therefore, providing digital literacy and understanding of reproductive health at this age is very important to form a strong character. Students can understand how digital literacy and knowledge of reproductive health affect adolescent character, and can evaluate the effectiveness of character building programs that integrate digital literacy and reproductive health.